Keroncong : The Creativity Process of Pesona Gabuse Music Group in Pati Regency - Wismandanu, Hanur; Wadiyo, Wadiyo; Utomo, Udi (Catharsis, 2019)
The Keroncong Pesona Gabuse Group is one group that uses the Keroncong genre in every performance. To maintain its existence, Pesona Gabuse always presents new and contemporary works in every performance. This research analyzes the process of creativity in realizing new works as an effort to preserve keroncong music in the country. Thus the purpose of this study is to analyze how the processes of artists in creativity, especially the personnel of the Pesona Gabuse group, using qualitative research methods. Data collection techniques using observation techniques, interviews, and document studies. The data validity technique is by using data and source triangulation, while the data analysis procedure is by data reduction, data presentation, and drawing conclusions. The theory used to analyze the data that is the theory of Creativity according to Utami Munandar. It is defined into four types of dimensions as "four points creativity" namely (1) personal dimensions (person), (2) dimensions of the process (process), (3) dimensions of pressure (press), and product dimensions. The general result found is that there is a culture which is the result of a form of community gratitude because of the abundant of natural resources, or art that is only intended as mere entertainment. The art and culture tours in general are the Gong Theater, Widyas Budoyo dance studio, shadow puppet shows, puppet shows, barongsai pagoda, alms earth, and the Gabus market festival. One of them is music tour, there are 2 music tours in the village of Gabus namely Gagego music village and Pesona Gabuse. The Pesona Gabuse Keroncong Group is one of the existing keroncong groups in Pati Regency. Specific research results found relating to the creativity process are the result of the creative process of the Keroncong Pesona Gabuse music group. Keroncong Pesona Gabuse group makes the keroncong music sound different from the original keroncong music that has been legendary since the Indonesian colonial era, such as the original keroncong and extra keroncong which are almost all rhythmic 4/4 music. The new genre created by the Pesona Gabuse group is pop keroncong, congdut (dangdut keroncong), congrock (rock keroncong, congska (ska keroncong), reggae keroncong, and congjazz (jazz keroncong).